The Laminin Receptors Basal Cell Adhesion Molecule/Lutheran and Integrin α7β1 on Human Hematopoietic Stem Cells - Godavarthy, Parimala Sonika; Walter, Christina B.; Lengerke, Claudia; Klein, Gerd (Frontiers in Cell and Developmental Biology, 2021)
In the adult organism, hematopoietic stem and progenitor cells (HSPC) reside in the bone marrow (BM) in specialized hematopoietic stem cell niches of which the extracellular matrix (ECM) is an integral component. Laminins (LM) are a family of heterotrimeric ECM molecules of which mainly family members containing an α4 or α5 chain are expressed in cells from BM niches and involved in HSPC homing and proliferation. Various integrin and non-integrin laminin receptors have been identified and characterized. Among these, the integrins α6β1 and α3β1 were reported to be strongly expressed on human and mouse HSPC. In the present study, we focus on two further specific laminin receptors, namely integrin α7β1 and basal cell adhesion molecule/Lutheran (BCAM/Lu). Using RT-PCR analyses, immunofluorescence staining, immunoblotting and flow cytometry, we show that both are strongly expressed by human lineage-negative CD34 + HSPC. Treatment with function-blocking antibodies against BCAM/Lu neither inhibits the strong adhesive interaction of CD34 + HSPC with LM-511/LM-521 nor the LM-511/LM-521 mediated changes in CD34 + HSPC proliferation, but however, influences the cytokine-induced differentiation of HSPC in colony formation assays. In addition, stromal-derived factor (SDF) 1α-mediated transmigration of CD34 + HSPC through an endothelial cell layer was effectively diminished by BCAM/Lu antibodies, suggesting a direct involvement of BCAM/Lu in the migration process. This study indicates that both laminin receptors newly identified on human CD34 + HSPC should be taken into consideration in future studies.